Potential of Modification of Techno-Functional Properties and Structural Characteristics of Citrus, Apple, Oat, and Pea Dietary Fiber by High-Intensity Ultrasound - Ann-Marie Kalla-Bertholdt; Anne Kathrin Baier; Cornelia Rauh (Foods, 2023)
Plant fibers are rich in dietary fiber and micronutrients but often exhibit poor functionality. Ultrasonication can affect the particle size of plant fiber, thereby influencing other techno-functional properties. Therefore, this study aimed to investigate the effects of high-intensity ultrasound on citrus, apple, oat, and pea fiber. Initially, solutions containing 1 wt% of plant fiber were homogenized using ultrasonication (amplitude 116 µm, t = 150 s, energy density = 225 kJ/L, <semantics><mover accent="true">P¯</mover> </semantics>= 325 W). Due to cavitation effects induced by ultrasound, differences in particle size and a shift in the ratio of insoluble and alcohol-insoluble fractions for dietary fiber were observed. Additionally, viscosities for citrus and apple fiber increased from 1.4 Pa·s to 84.4 Pa·s and from 1.34 Pa·s to 31.7 Pa·s, respectively, at shear rates of 100 <semantics>1s</semantics>. This was attributed to observed differences in the microstructure. Freeze-dried samples of purified citrus and apple fiber revealed thin and nearly transparent layers, possibly contributing to enhanced water binding capacity and, therefore, increased viscosity. Water binding capacity for citrus fiber increased from 18.2 g/g to 41.8 g/g, and a 40% increase was observed for apple fiber. Finally, ultrasound demonstrated itself be an effective technology for modifying the techno-functional properties of plant fiber, such as water binding capacity.